Growing Complexities in Marketing with Special Reference to Customer Engagement - Gagan Bhatia (2018)
Customer engagement is a business communication connection between an external stakeholder and an organization through various channels of correspondence.Emerging phenomenon witnesses complex factors governing the choices of producers and consumers. Intense competition is set in both quality of the product and price.The degree to which a company succeeds in creating an intimate long-term relationship with the customer or external stakeholder. The research article indicates that companies are going beyond traditional customer satisfaction or relationship programmes to develop new ways to ensure that customers are engaged in all of their interactions with the company.
Keywords: Management